2001
DOI: 10.1103/physrevb.64.233321
|View full text |Cite
|
Sign up to set email alerts
|

Classical mechanism for negative magnetoresistance in two dimensions

Abstract: The classical two-dimensional problem of non-interacting electrons scattered by short-range impurity centers in the presence of magnetic field is investigated both analytically and numerically. A strong magnetoresistance exists in such a system, due to freely circling electrons, which are not taken into account by the Boltzmann-Drude approach. A parabolic magnetoresistance is found at low fields.Comment: 4 pages, 3 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
71
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 19 publications
5
71
2
1
Order By: Relevance
“…3 In the same inset we show the values of F σ 0 determined from the magnetoresistance treatment. Some difference between F σ 0 -values obtained by the different ways can be sequence of the classical magnetoresistance mechanisms, 27,28,29,30 which are not essential in our case, but, nevertheless, can influence the shape of the ρ xx -curve.…”
mentioning
confidence: 72%
“…3 In the same inset we show the values of F σ 0 determined from the magnetoresistance treatment. Some difference between F σ 0 -values obtained by the different ways can be sequence of the classical magnetoresistance mechanisms, 27,28,29,30 which are not essential in our case, but, nevertheless, can influence the shape of the ρ xx -curve.…”
mentioning
confidence: 72%
“…As a prominent example, memory effects in magnetotransport of composite fermions subject to an effective smooth random magnetic field explain a positive MR around half-filling of the lowest Landau level 7 . Another type of memory effects taking place in systems with rare strong scatterers is responsible for a negative MR in disordered antidot arrays 3,4,5,8,9 . However, such effects turn out to be of a relatively minor importance for the low-field quasiclassical magnetotransport in semiconductor heterostructures with typical experimental parameters, while at higher B they are obscured by the development of the Shubnikovde Haas oscillation (SdHO).…”
Section: Introductionmentioning
confidence: 99%
“…There are several distinct sources of a nontrivial MR, which reflect the rich physics of the magnetotransport in 2D systems. First of all, it has been recognized recently that even within the quasiclassical theory memory effects may lead to strong MR 3,4,5,6,7,8,9 . The essence of such effects is that a particle "keeps memory" about the presence (or absence) of a scatterer in a spatial region which it has already visited.…”
Section: Introductionmentioning
confidence: 99%
“…However, for B = 0 the role of ME is dramatically increased due to a strong dependence of return probability on B. Recent studies demonstrated that ME lead to a variety of nontrivial magnetotransport phenomena in 2D disordered systems such as magnetic-field-induced classical localization [7,8], high-field negative [7,8,9,10,11] and positive MR [12], low-field anomalous MR [13,14,15], and non-Lorentzian shape of cyclotron resonance [16].…”
mentioning
confidence: 99%